Boron nitride / polydopamine / porous graphene modified foam as well as preparation method and application thereof
By preparing boron nitride/polydopamine/porous graphene modified foam, the problem of insufficient thermal conductivity and wave absorption performance of polymer materials in electronic devices is solved, and efficient thermal conductivity and wave absorption performance are achieved.
Patent Information
- Application Number
- CN202411971669.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-25
AI Technical Summary
The existing polymer materials in electronic devices have limited their wide application in the microelectronic packaging industry due to their low thermal conductivity and lack of electromagnetic wave absorption capabilities.
By preparing boron nitride/polydopamine/poly graphene modified foam, the thermal conductivity of boron nitride and the absorbance of porous graphene are utilized, and the self-polymerization of polydopamine is combined to form a composite material integrating the absorbance-thermal conductivity.
It has achieved significantly improved the thermal conductivity and wave absorption performance of the material at a lower filling amount, with a thermal conductivity of ≥1.98W/m·K, an effective absorption bandwidth of 6.76GHz, and a reflection loss of -54.30dB.
Smart Images

Figure CN119684673A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electromagnetic absorbing materials and thermal interface materials, and in particular to a boron nitride / polydopamine / porous graphene modified foam and a preparation method and application thereof. Background Art
[0002] With the innovation of third-generation semiconductor technology and the trend of electronic products towards miniaturization, lightweight and high integration, the electromagnetic interference and the resulting heat accumulation in the narrow space inside the device seriously affect the original reliability and stability of the device. With the maturity of 5G communication technology and the upcoming 6G era, the heat dissipation and electromagnetic compatibility inside high-density integrated circuits have become more challenging. Therefore, it is urgent to design a gasket with both efficient electromagnetic wave absorption and excellent thermal conductivity to conduct excess energy to the outside world.
[0003] Polymers such as polydimethylsiloxane (PDMS), epoxy resin (EP), polyimide (PI), polyurethane (PU), etc. are widely used in sealing and interface connection of various electronic devices due to their excellent mechanical properties, insulation properties and unique chemical stability. However, the thermal conductivity of polymer materials is usually very low (generally less than 0.2W / m·K), and they also do not have the ability to absorb electromagnetic waves, which greatly limits the widespread application of polymers in the microelectronic packaging industry. Adding high thermal conductivity fillers (such as carbon materials, ceramic-based materials, and metal particles, etc.) and absorbing fillers (such as magnetic metal compounds ferrite, carbon materials, conductive polymers, etc.) to polymer materials is a common method to improve the absorbing and thermal conductivity of materials. However, a large amount of fillers often need to be added to composite materials to achieve satisfactory results, which will greatly reduce the excellent mechanical and mechanical properties of the polymer matrix while increasing the manufacturing process. Therefore, it is of great significance to reduce the amount of functional fillers added to polymers in high power density electronic devices.
[0004] Preformed 3D interconnected filler networks have attracted attention due to their low interfacial thermal resistance and their ability to reliably achieve significant thermal conductivity improvements at low filler loadings. Common preparation methods such as ice templates and chemical vapor deposition are time-consuming and complex, making them difficult to meet the requirements of large-scale production. Low-density, low-porosity commercial polymer foams (such as melamine foams, polyurethane foams, etc.) are a type of preformed skeleton material that can be easily obtained. They are economically priced and widely used, and have been widely studied in recent years.
[0005] Hexagonal boron nitride (h-BN), also known as "white graphene" due to its high thermal conductivity, chemical stability, electrical insulation and optical transparency, has received great attention in recent years. Studies have found that the thermal expansion coefficient of polymer-based composites containing boron nitride is significantly reduced, its mechanical properties are improved, and the stability of dielectric properties over a wide temperature and frequency range is also improved. However, due to its poor dispersibility, agglomeration often occurs in the polymer, resulting in a lack of significant improvement in thermal conductivity.
[0006] As a typical two-dimensional carbon nanomaterial, graphene has been the focus and hotspot in the field of new materials research in recent years. Its rich porous structure, good conductivity and high thermal stability are expected to become a new generation of absorbing materials. However, single graphene materials cannot achieve high absorption efficiency for electromagnetic waves and cannot meet actual needs in many scenarios. Therefore, it is usually necessary to further compound graphene with other materials to meet the use requirements of specific application scenarios. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide a boron nitride / polydopamine / porous graphene modified foam and a preparation method thereof. The obtained boron nitride / polydopamine / porous graphene modified foam has both efficient electromagnetic wave absorption performance and thermal conductivity when used as a wave absorbing and thermal conductive material, and exhibits excellent performance in electronic equipment.
[0008] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:
[0009] The first object of the present invention is to provide a method for preparing a boron nitride / polydopamine / porous graphene modified foam, comprising the following steps:
[0010] (1) immersing the polymer foam in a modified boron nitride solution and freeze-drying the solution to obtain a boron nitride modified foam;
[0011] (2) immersing the boron nitride modified foam in a dopamine solution and vacuum drying to obtain a boron nitride / polydopamine modified foam;
[0012] (3) irradiating the carbon-containing film with a laser and scraping off the formed three-dimensional porous graphene to obtain porous graphene;
[0013] (4) Immersing the boron nitride / polydopamine modified foam in a porous graphene solution and vacuum drying to obtain a boron nitride / polydopamine / porous graphene modified foam.
[0014] During the impregnation process, the foam can be squeezed and stirred or ultrasonically treated to make the foam fully contact with the impregnation solution, thereby increasing the loading amount of the loaded substance on the foam.
[0015] In step (1), the polymer foam includes but is not limited to at least one of melamine foam and polyurethane foam.
[0016] In step (1), the polymer foam is treated with a silane coupling agent to provide the foam surface with silanol groups. Further, the silane coupling agent includes but is not limited to at least one of KH-550, KH-551, and KH-560. Preferably, the silane coupling agent is an aqueous solution of a silane coupling agent with a concentration of 0.02 to 0.1 g / mL.
[0017] In step (1), the modified boron nitride is hydroxyl boron nitride, which is obtained by treating hexagonal boron nitride with a strong base, in order to make the h-BN surface carry hydroxyl groups. Furthermore, the strong base includes but is not limited to at least one of sodium hydroxide, potassium hydroxide, calcium hydroxide, and barium hydroxide; the particle size of the hexagonal boron nitride is 1 to 2 μm; the concentration of the strong base is 5 to 10 mol / L, the treatment temperature is 80 to 120°C, and the treatment time is 8 to 16 hours. Preferably, the modified boron nitride solution is a hydroxyl boron nitride aqueous solution with a concentration of 2 to 10 mg / mL. After being modified with hydroxyl groups, h-BN can be organically bonded with the relevant functional groups on the foam skeleton, orderly dispersed to form a heat conduction path, which is conducive to maximizing the role of the thermal conductive filler.
[0018] In step (1), the purpose of freeze drying is to keep the original foam skeleton structure intact.
[0019] In step (2), the dopamine solution includes dopamine hydrochloride and Tris buffer. Furthermore, the dosage ratio of dopamine hydrochloride to Tris buffer is (0.05-0.15) g:25 mL; the pH value of the Tris buffer is 7.5-8.5. Dopamine will hydrolyze and self-polymerize at room temperature to form polydopamine, which can enhance the interfacial compatibility between graphene and boron nitride modified foam. Adding polydopamine to the boron nitride thermal conductive skeleton can make porous graphene attached to the surface of the thermal conductive skeleton. This special structure is conducive to achieving excellent microwave absorption performance under the premise of high thermal conductivity through interface polarization and balancing dielectric loss and magnetic loss. In addition, the mixed filler network formed by boron nitride and graphene can also provide certain help for heat transfer.
[0020] In step (3), the carbon-containing film is a film made of at least one of a synthetic high molecular polymer and a natural high molecular polymer. Preferably, the carbon-containing film is a film made of a synthetic high molecular polymer, a natural high molecular polymer and a metal salt. Furthermore, the synthetic high molecular polymer includes but is not limited to at least one of polyethersulfone, polyimide, polyethylene terephthalate, polystyrene, and phenolic resin; the natural high molecular polymer includes but is not limited to at least one of lignin, cellulose, starch, polysaccharide, chitosan, chitosan and its derivatives; the metal salt includes but is not limited to at least one of iron salt, nickel salt, copper salt and molybdenum salt. The composite of elements such as iron, nickel, copper, and molybdenum with three-dimensional porous graphene can improve the wave absorption performance of the material.
[0021] In step (3), the laser is at least one of a fiber laser, a solid laser, a gas laser, a semiconductor laser, and a liquid laser.
[0022] In step (3), the power of the laser irradiation is 16 to 25 W, the scanning speed is 180 to 450 mm / s, the jump speed is 100 to 1000 mm / s, the Q frequency is 1 to 10 kHz, the scanning line spacing is 0.06 to 0.12 mm, the spot size is 60 to 100 μm, and the focal length is set to 0.5 to 3 mm above the surface of the film.
[0023] The second object of the present invention is to provide a boron nitride / polydopamine / porous graphene modified foam prepared by the method for preparing the boron nitride / polydopamine / porous graphene modified foam.
[0024] The third object of the present invention is to provide the use of the boron nitride / polydopamine / porous graphene modified foam as a wave absorbing and heat conducting material.
[0025] A fourth object of the present invention is to provide a wave-absorbing and heat-conducting silicone rubber, which comprises silicone rubber and the boron nitride / polydopamine / porous graphene modified foam.
[0026] The fifth object of the present invention is to provide a method for preparing wave-absorbing heat-conducting silicone rubber, wherein the boron nitride / polydopamine / porous graphene modified foam is firstly cast with liquid silicone rubber, and then heated and vulcanized to obtain the wave-absorbing heat-conducting silicone rubber.
[0027] Furthermore, the liquid silicone rubber is mixed with vinyl silicone oil, hydrogen-containing silicone oil, MQ silicone resin, inhibitor and catalyst. Furthermore, the inhibitor includes but is not limited to at least one of vinyl ring body and acetylene alcohol; the catalyst is selected from at least one of platinum catalyst and organic tin catalyst; the mass ratio of the vinyl silicone oil, hydrogen-containing silicone oil, MQ silicone resin, inhibitor and catalyst is 100: (14.67-17.34): (10.88-12.68): (0.05-0.08): (0.05-0.15).
[0028] Furthermore, the heating vulcanization is carried out in a vacuum drying oven, firstly vacuuming at room temperature for 1 to 3 hours and then heating to 100 to 120° C. and vacuuming for 1 to 3 hours.
[0029] The present invention uses a three-dimensional porous foam skeleton to load modified boron nitride to construct a continuous heat conduction path, which increases the contact area with the air while ensuring efficient thermal conductivity, and improves the overall impedance matching characteristics of the material; at the same time, it provides a substrate for loading porous graphene, and uses the self-polymerization of dopamine and the interaction with the functional groups on the surface of graphene to evenly disperse the graphene on the foam skeleton. The evenly dispersed porous graphene greatly improves the material's absorption capacity for electromagnetic waves through mechanisms such as conductivity loss, polarization loss, magnetic loss, and multiple internal reflection and refraction, and also plays a role in assisting heat transfer, thereby achieving a common improvement in wave absorption and thermal conductivity.
[0030] The beneficial effects of the present invention are:
[0031] 1. The present invention combines chemically modified hexagonal boron nitride and polymer foam modified by silane coupling agent through covalent bonds to form a continuous three-dimensional thermal conductive path. The excellent thermal conductivity of boron nitride is demonstrated with the help of the successful construction of the thermal conductive path with the minimum filler content. Due to the porous nature of the foam itself, the impedance matching characteristics of the entire material are greatly improved, which is beneficial to the loss of electromagnetic waves.
[0032] 2. The present invention directly synthesizes three-dimensional porous graphene or magnetic metal oxide nanoparticles / porous graphene composites on a carbon-containing film in one step by laser irradiation. Compared with the wet chemical preparation route of powdered graphene, the laser irradiation method can significantly improve the processing power, and the prepared magnetic metal oxide nanoparticles / porous graphene can dissipate electromagnetic waves through various loss mechanisms such as conductivity loss, polarization loss, magnetic coupling effect and eddy current loss.
[0033] 3. The present invention combines the constructed boron nitride thermal conductive path with the porous graphene absorber through polydopamine to form a composite material integrating thermal absorption and thermal conductivity. The composite material can achieve a significant improvement in thermal conductivity at a relatively low filling amount (25wt%), with a thermal conductivity coefficient of ≥1.98W / m·K (approximately 9.8 times that of ordinary polymers), and has excellent absorbing performance. At 2.5mm, the effective absorption bandwidth can reach 6.76GHz, and the minimum reflection loss can reach -54.30dB, that is, the effective absorption rate of electromagnetic waves can reach 99.9999%. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is an electron microscope image of the magnetic ferroferric oxide / porous graphene prepared in Example 1 of the present invention;
[0035] Figure 2 Electron micrographs of hydroxyl-modified boron nitride (a) and boron nitride-modified foam (b) prepared in Example 1 of the present invention;
[0036] Figure 3 This is an electron microscope image of the boron nitride / polydopamine / porous graphene modified foam prepared in Example 1 of the present invention;
[0037] Figure 4 This is a diagram of the wave absorbing performance of the silicone rubber prepared in Example 1 of the present invention;
[0038] Figure 5 This is a graph showing the temperature variation over time of the silicone rubber and melamine foam prepared in Example 1 of the present invention under an infrared camera. DETAILED DESCRIPTION
[0039] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments and diagrams.
[0040] The raw materials in the following examples and comparative examples are described:
[0041] Melamine foam: density 5kg / m 3 , thickness 2mm, size 10mm×10mm×2mm;
[0042] h-BN: particle size 1-2 μm;
[0043] Vinyl silicone oil: Model JP-01V-1000;
[0044] Hydrogenated silicone oil: hydrogen content 0.8%, viscosity 200mm 2 / s, pH = 7;
[0045] MQ Silicone: Model 5201S.
[0046] Example 1
[0047] 1) The melamine foam was immersed in a KH-550 aqueous solution (0.05 g / mL) and stirred for 2 h to obtain a melamine foam having a silane coupling agent on the surface.
[0048] 2) Weigh 2 g of h-BN and pour it into a sodium hydroxide solution (10 mol / L), heat it to 120°C and keep it warm for 12 h to obtain hydroxyl-modified boron nitride (BN-OH).
[0049] 3) The melamine foam containing a silane coupling agent on the surface was immersed in a BN-OH solution (4 mg / mL), the foam was squeezed to make the two fully contact, stirred for 4 hours, and freeze-dried to obtain a boron nitride modified foam.
[0050] 4) Weigh 0.05 g of dopamine hydrochloride and pour it into 25 mL of Tris buffer (pH = 7.8), then immerse the boron nitride modified foam obtained in step (3), stir for 4 hours, and vacuum dry to obtain a boron nitride modified foam coated with polydopamine on the surface, i.e., a boron nitride / polydopamine modified foam.
[0051] 5) Polyethersulfone, sodium lignin sulfonate, ferric chloride hexahydrate and N,N-dimethylacetamide were blended in a mass ratio of 25:17:10:100 and cast on a glass plate to form a carbon-containing film. The film was then irradiated with a CO2 laser, with the focal length set to 3 mm above the film surface, the laser power of 20 W, the scanning speed of 360 mm / s, the air jump speed of 1000 mm / s, the Q frequency of 1 Hz, the scanning line spacing of 0.1 mm, and the laser spot size of 60 μm. The three-dimensional porous graphene formed on the film surface was scraped off to obtain magnetic ferroferric oxide / porous graphene.
[0052] 6) immersing the boron nitride / polydopamine modified foam in a magnetic ferroferric oxide / porous graphene solution (5 mg / mL), ultrasonically treating for 6 h at a power of 100 W, and vacuum drying to obtain a boron nitride / polydopamine / porous graphene modified foam.
[0053] 7) Vinyl silicone oil, hydrogen silicone oil, MQ silicone resin, 1-ethynyl cyclohexanol (defoaming agent) and chloroplatinic acid (platinum catalyst) were mixed in a mass ratio of 100:14.67:10.88:0.05:0.15 to obtain a uniform liquid silicone rubber. The liquid silicone rubber was then poured on the boron nitride / polydopamine / porous graphene modified foam, and then placed in a vacuum drying oven, first vacuumed at room temperature for 1 hour, then heated to 120°C and vacuumed for 3 hours, and finally cut into thin sheets.
[0054] Example 2
[0055] 1) The melamine foam was immersed in a KH-550 aqueous solution (0.02 g / mL) and stirred for 2 h to obtain a melamine foam having a silane coupling agent on the surface.
[0056] 2) Weigh 2 g h-BN and pour it into a sodium hydroxide solution (5 mol / L), heat it to 100°C and keep it warm for 12 h to obtain hydroxyl-modified boron nitride (BN-OH).
[0057] 3) The melamine foam containing a silane coupling agent on the surface was immersed in a BN-OH solution (2 mg / mL), the foam was squeezed to allow the two to fully contact, stirred for 4 hours, and freeze-dried to obtain a boron nitride modified foam.
[0058] 4) Weigh 0.05 g of dopamine hydrochloride and pour it into 25 mL of Tris buffer (pH = 8.2), then immerse the boron nitride modified foam obtained in step (3), stir for 2 h, and vacuum dry to obtain a boron nitride modified foam coated with polydopamine on the surface, i.e., a boron nitride / polydopamine modified foam.
[0059] 5) Polyethersulfone, sodium lignin sulfonate, ferric chloride hexahydrate and N,N-dimethylacetamide were blended in a mass ratio of 25:17:5:100 and cast on a glass plate to form a carbon-containing film. The film was then irradiated with a CO2 laser, with the focal length set to 2.5 mm above the film surface, the laser power of 15 W, the scanning speed of 360 mm / s, the air jump speed of 1000 mm / s, the Q frequency of 1 Hz, the scanning line spacing of 0.1 mm, and the laser spot size of 80 μm. The three-dimensional porous graphene formed on the film surface was scraped off to obtain magnetic ferroferric oxide / porous graphene.
[0060] 6) immersing the boron nitride / polydopamine modified foam in a magnetic ferroferric oxide / porous graphene solution (3 mg / mL), ultrasonically treating it at a power of 100 W for 6 h, and vacuum drying it to obtain a boron nitride / polydopamine / porous graphene modified foam.
[0061] 7) Vinyl silicone oil, hydrogen silicone oil, MQ silicone resin, 1-ethynyl cyclohexanol (defoaming agent) and dibutyltin dilaurate (platinum catalyst) were mixed in a mass ratio of 100:14.67:10.88:0.05:0.15 to obtain a uniform liquid silicone rubber. The liquid silicone rubber was then poured on the boron nitride / polydopamine / porous graphene modified foam, and then placed in a vacuum drying oven, first vacuumed at room temperature for 1 hour, then heated to 120°C and vacuumed for 3 hours, and finally cut into thin sheets.
[0062] Example 3
[0063] 1) The melamine foam was immersed in a KH-550 aqueous solution (0.08 g / mL) and stirred for 2 h to obtain a melamine foam having a silane coupling agent on the surface.
[0064] 2) Weigh 2 g of h-BN and pour it into a sodium hydroxide solution (15 mol / L), heat it to 80°C and keep it warm for 12 h to obtain hydroxyl-modified boron nitride (BN-OH).
[0065] 3) The melamine foam containing a silane coupling agent on the surface was immersed in a BN-OH solution (6 mg / mL), the foam was squeezed to make the two fully contact, stirred for 4 hours, and freeze-dried to obtain a boron nitride modified foam.
[0066] 4) Weigh 0.05 g of dopamine hydrochloride and pour it into 25 mL of Tris buffer (pH = 8.5), then immerse the boron nitride modified foam obtained in step (3), stir for 2 h, and vacuum dry to obtain a boron nitride modified foam coated with polydopamine on the surface, i.e., a boron nitride / polydopamine modified foam.
[0067] 5) Polyethersulfone, sodium lignin sulfonate, ferric chloride hexahydrate and N,N-dimethylacetamide were blended in a mass ratio of 25:17:7:100 and cast on a glass plate to form a carbon-containing film. The film was then irradiated with a CO2 laser, with the focal length set to 2.5 mm above the film surface, the laser power of 30 W, the scanning speed of 360 mm / s, the air jump speed of 1000 mm / s, the Q frequency of 1 Hz, the scanning line spacing of 0.1 mm, and the laser spot size of 100 μm. The three-dimensional porous graphene formed on the surface of the film was scraped off to obtain magnetic ferroferric oxide / porous graphene.
[0068] 6) immersing the boron nitride / polydopamine modified foam in a magnetic ferroferric oxide / porous graphene solution (3 mg / mL), ultrasonically treating it at a power of 100 W for 6 h, and vacuum drying it to obtain a boron nitride / polydopamine / porous graphene modified foam.
[0069] 7) Vinyl silicone oil, hydrogenated silicone oil, MQ silicone resin, vinyl ring (defoaming agent) and chloroplatinic acid (platinum catalyst) were mixed in a mass ratio of 100:14.67:10.88:0.05:0.15 to obtain a uniform liquid silicone rubber. The liquid silicone rubber was then poured on the boron nitride / polydopamine / porous graphene modified foam, and then placed in a vacuum drying oven, first vacuumed at room temperature for 3 hours, then heated to 120°C and vacuumed for 1 hour, and finally cut into thin sheets.
[0070] Example 4
[0071] 1) The polyurethane foam was immersed in a KH-550 aqueous solution (0.05 g / mL) and stirred for 2 h to obtain a polyurethane foam having a silane coupling agent on the surface.
[0072] 2) Weigh 2 g of h-BN and pour it into a sodium hydroxide solution (10 mol / L), heat it to 120°C and keep it warm for 12 h to obtain hydroxyl-modified boron nitride (BN-OH).
[0073] 3) The polyurethane foam containing the silane coupling agent on the surface was immersed in the BN-OH solution (4 mg / mL), the foam was squeezed to make the two fully contact, stirred for 4 hours, and freeze-dried to obtain the boron nitride modified foam.
[0074] 4) Weigh 0.05 g of dopamine hydrochloride and pour it into 25 mL of Tris buffer (pH = 7.8), then immerse the boron nitride modified foam obtained in step (3), stir for 4 hours, and vacuum dry to obtain a boron nitride modified foam coated with polydopamine on the surface, i.e., a boron nitride / polydopamine modified foam.
[0075] 5) Polyethersulfone, sodium lignin sulfonate, ferric chloride hexahydrate and N,N-dimethylacetamide were blended in a mass ratio of 25:17:10:100 and cast on a glass plate to form a carbon-containing film. The film was then irradiated with a CO2 laser, with the focal length set to 3 mm above the film surface, the laser power of 20 W, the scanning speed of 360 mm / s, the air jump speed of 1000 mm / s, the Q frequency of 1 Hz, the scanning line spacing of 0.1 mm, and the laser spot size of 60 μm. The three-dimensional porous graphene formed on the film surface was scraped off to obtain magnetic ferroferric oxide / porous graphene.
[0076] 6) immersing the boron nitride / polydopamine modified foam in a magnetic ferroferric oxide / porous graphene solution (5 mg / mL), ultrasonically treating for 6 h at a power of 100 W, and vacuum drying to obtain a boron nitride / polydopamine / porous graphene modified foam.
[0077] 7) Vinyl silicone oil, hydrogen silicone oil, MQ silicone resin, 1-ethynyl cyclohexanol (defoaming agent) and chloroplatinic acid (platinum catalyst) were mixed in a mass ratio of 100:14.67:10.88:0.05:0.15 to obtain a uniform liquid silicone rubber. The liquid silicone rubber was then poured on the boron nitride / polydopamine / porous graphene modified foam, and then placed in a vacuum drying oven, first vacuumed at room temperature for 1 hour, then heated to 120°C and vacuumed for 3 hours, and finally cut into thin sheets.
[0078] Example 5
[0079] 1) The melamine foam was immersed in a KH-550 aqueous solution (0.02 g / mL) and stirred for 2 h to obtain a melamine foam having a silane coupling agent on the surface.
[0080] 2) Weigh 2 g h-BN and pour it into a sodium hydroxide solution (5 mol / L), heat it to 100°C and keep it warm for 12 h to obtain hydroxyl-modified boron nitride (BN-OH).
[0081] 3) The melamine foam containing a silane coupling agent on the surface was immersed in a BN-OH solution (2 mg / mL), the foam was squeezed to allow the two to fully contact, stirred for 4 hours, and freeze-dried to obtain a boron nitride modified foam.
[0082] 4) Weigh 0.05 g of dopamine hydrochloride and pour it into 25 mL of Tris buffer (pH = 8.2), then immerse the boron nitride modified foam obtained in step (3), stir for 2 h, and vacuum dry to obtain a boron nitride modified foam coated with polydopamine on the surface, i.e., a boron nitride / polydopamine modified foam.
[0083] 5) Polyethersulfone, sodium lignin sulfonate and N,N-dimethylacetamide were blended in a mass ratio of 25:17:100 and cast on a glass plate to form a carbon-containing film. The film was then irradiated with a CO2 laser, with the focal length set to 2.5 mm above the film surface, the laser power of 15 W, the scanning speed of 360 mm / s, the air jump speed of 1000 mm / s, the Q frequency of 1 Hz, the scanning line spacing of 0.1 mm, and the laser spot size of 80 μm. The three-dimensional porous graphene formed on the film surface was scraped off to obtain porous graphene.
[0084] 6) immersing the boron nitride / polydopamine modified foam into a porous graphene solution (3 mg / mL), ultrasonically treating the solution at a power of 100 W for 6 h, and vacuum drying the solution to obtain a boron nitride / polydopamine / porous graphene modified foam.
[0085] 7) Vinyl silicone oil, hydrogen silicone oil, MQ silicone resin, 1-ethynyl cyclohexanol (defoaming agent) and dibutyltin dilaurate (platinum catalyst) were mixed in a mass ratio of 100:14.67:10.88:0.05:0.15 to obtain a uniform liquid silicone rubber. The liquid silicone rubber was then poured on the boron nitride / polydopamine / porous graphene modified foam, and then placed in a vacuum drying oven, first vacuumed at room temperature for 1 hour, then heated to 120°C and vacuumed for 3 hours, and finally cut into thin sheets.
[0086] Comparative Example 1
[0087] 1) The melamine foam was immersed in a KH-550 aqueous solution (0.02 g / mL) and stirred for 2 h to obtain a melamine foam having a silane coupling agent on the surface.
[0088] 2) Immerse the melamine foam containing a silane coupling agent on the surface into an h-BN solution (2 mg / mL), squeeze the foam to allow the two to fully contact, stir for 4 hours, and freeze-dry to obtain a boron nitride modified foam.
[0089] 3) Weigh 0.05 g of dopamine hydrochloride and pour it into 25 mL of Tris buffer (pH = 8.2), then immerse the boron nitride modified foam obtained in step (2), stir for 2 h, and vacuum dry to obtain a boron nitride modified foam coated with polydopamine on the surface, i.e., a boron nitride / polydopamine modified foam.
[0090] 4) Polyethersulfone, sodium lignin sulfonate, ferric chloride hexahydrate and N,N-dimethylacetamide were blended in a mass ratio of 25:17:5:100 and cast on a glass plate to form a carbon-containing film. The film was then irradiated with a CO2 laser, with the focal length set to 2.5 mm above the film surface, the laser power of 15 W, the scanning speed of 360 mm / s, the air jump speed of 1000 mm / s, the Q frequency of 1 Hz, the scanning line spacing of 0.1 mm, and the laser spot size of 80 μm. The three-dimensional porous graphene formed on the film surface was scraped off to obtain magnetic ferroferric oxide / porous graphene.
[0091] 5) immersing the boron nitride / polydopamine modified foam in a magnetic ferroferric oxide / porous graphene solution (3 mg / mL), ultrasonically treating it at a power of 100 W for 6 h, and vacuum drying it to obtain a boron nitride / polydopamine / porous graphene modified foam.
[0092] 6) Vinyl silicone oil, hydrogen silicone oil, MQ silicone resin, 1-ethynyl cyclohexanol (defoaming agent) and dibutyltin dilaurate (platinum catalyst) were mixed in a mass ratio of 100:14.67:10.88:0.05:0.15 to obtain a uniform liquid silicone rubber. The liquid silicone rubber was then poured on the boron nitride / polydopamine / porous graphene modified foam, and then placed in a vacuum drying oven, first vacuumed at room temperature for 1 hour, then heated to 120°C and vacuumed for 3 hours, and finally cut into thin sheets.
[0093] Comparative Example 2
[0094] 1) The melamine foam was immersed in a KH-550 aqueous solution (0.02 g / mL) and stirred for 2 h to obtain a melamine foam having a silane coupling agent on the surface.
[0095] 2) Weigh 2 g h-BN and pour it into a sodium hydroxide solution (5 mol / L), heat it to 100°C and keep it warm for 12 h to obtain hydroxyl-modified boron nitride (BN-OH).
[0096] 3) The melamine foam containing a silane coupling agent on the surface was immersed in a BN-OH solution (2 mg / mL), the foam was squeezed to make the two fully contact, stirred for 4 hours, and freeze-dried for 1 day to obtain a boron nitride modified foam.
[0097] 4) Polyethersulfone, sodium lignin sulfonate, ferric chloride hexahydrate and N,N-dimethylacetamide were blended in a mass ratio of 25:17:5:100 and cast on a glass plate to form a carbon-containing film. The film was then irradiated with a CO2 laser, with the focal length set to 2.5 mm above the film surface, the laser power of 15 W, the scanning speed of 360 mm / s, the air jump speed of 1000 mm / s, the Q frequency of 1 Hz, the scanning line spacing of 0.1 mm, and the laser spot size of 80 μm. The three-dimensional porous graphene formed on the film surface was scraped off to obtain magnetic ferroferric oxide / porous graphene.
[0098] 5) immersing the boron nitride modified foam in a magnetic ferroferric oxide / porous graphene solution (3 mg / mL), ultrasonically treating it at a power of 100 W for 6 h, and vacuum drying it to obtain a boron nitride / porous graphene modified foam.
[0099] 6) Vinyl silicone oil, hydrogen silicone oil, MQ silicone resin, 1-ethynyl cyclohexanol (defoaming agent) and dibutyltin dilaurate (platinum catalyst) were mixed in a mass ratio of 100:14.67:10.88:0.05:0.15 to obtain a uniform liquid silicone rubber. The liquid silicone rubber was then poured on the boron nitride / porous graphene modified foam, and then placed in a vacuum drying oven, first vacuumed at room temperature for 1 hour, then heated to 120°C and vacuumed for 3 hours, and finally cut into thin sheets.
[0100] Comparative Example 3
[0101] 1) The melamine foam was immersed in a KH-550 aqueous solution (0.02 g / mL) and stirred for 2 h to obtain a melamine foam having a silane coupling agent on the surface.
[0102] 2) Weigh 2 g h-BN and pour it into a sodium hydroxide solution (5 mol / L), heat it to 100°C and keep it warm for 12 h to obtain hydroxyl-modified boron nitride (BN-OH).
[0103] 3) The melamine foam containing a silane coupling agent on the surface was immersed in a BN-OH solution (2 mg / mL), the foam was squeezed to allow the two to fully contact, stirred for 4 hours, and freeze-dried to obtain a boron nitride modified foam.
[0104] 4) Weigh 0.05 g of dopamine hydrochloride and pour it into 25 mL of Tris buffer (pH = 8.2), then immerse the boron nitride modified foam obtained in step (3), stir for 2 h, and vacuum dry to obtain a boron nitride modified foam coated with polydopamine on the surface, i.e., a boron nitride / polydopamine modified foam.
[0105] 5) Vinyl silicone oil, hydrogen silicone oil, MQ silicone resin, 1-ethynyl cyclohexanol (defoaming agent) and dibutyltin dilaurate (platinum catalyst) were mixed in a mass ratio of 100:14.67:10.88:0.05:0.15 to obtain a uniform liquid silicone rubber. The liquid silicone rubber was then poured on the boron nitride / polydopamine modified foam, and then placed in a vacuum drying oven, first vacuumed at room temperature for 1 hour, then heated to 120°C and vacuumed for 3 hours, and finally cut into thin sheets.
[0106] The thermal conductivity and wave absorption performance of the thin film samples prepared in the above embodiments and comparative examples were tested, and the test results are shown in Table 1.
[0107] The thermal conductivity test was carried out using a Hot Disk method thermal conductivity tester according to ISO 22007-2 standard. Five thin film samples were tested in each group and the average value was taken.
[0108] Bandwidth and loss testing using a vector network analyzer.
[0109] Table 1
[0110]
[0111]
[0112] From Table 1 we can see that:
[0113] As the concentration of the modified boron nitride solution in which the foam is immersed increases, the loading amount of boron nitride on the foam skeleton increases, and the thermal conductivity of the material increases accordingly; when the concentration of the modified boron nitride solution is 4 mg / mL, the thermal conductivity of the material is the best; when the concentration continues to increase, boron nitride will produce local accumulation on the skeleton, resulting in a decrease in thermal conduction efficiency.
[0114] As the iron ion concentration in the carbon-containing film increases, the number of magnetic nanoparticles inside the porous graphene increases, and the magnetic loss capacity of the material is enhanced, resulting in improved material absorption performance; when the iron ion concentration in the carbon-containing film is 0.06 mol / L, the material's absorption performance is best; when the concentration continues to increase, the excessive content of magnetic nanoparticles inside the porous graphene leads to impedance mismatch, resulting in reduced material absorption performance.
[0115] After replacing melamine foam with polyurethane foam, the thermal conductivity and wave absorption performance of the material are reduced due to the difference in porosity and surface activity between polyurethane foam and melamine foam.
[0116] When ferric chloride hexahydrate is not added during the preparation of the carbon-containing film, the material's wave absorbing performance is reduced due to the material's lack of magnetic loss capacity.
[0117] If the boron nitride is not hydroxylated or the foam is not treated with polydopamine, the boron nitride loading on the foam skeleton is low due to the lack of bonding between active functional groups, and a continuous heat conduction path cannot be formed, resulting in reduced thermal conductivity of the material.
[0118] Without adding magnetic ferroferric oxide / porous graphene to the thermal conductive skeleton, the material as a whole only has the multiple reflection losses of the foam thermal conductive skeleton and lacks more effective loss means, resulting in reduced wave absorption performance of the material.
[0119] from Figure 1 It can be seen from a that the surface of the magnetic Fe3O4 / porous graphene synthesized in situ on the carbon-containing film by laser action has pore sizes of varying sizes; Figure 1 b It can be seen that ferroferric oxide is distributed on graphene.
[0120] from Figure 2 It can be seen from a that the hexagonal boron nitride modified by hydroxyl groups is a thin sheet with uniform thickness; Figure 2 b It can be seen that after the hydroxyl-modified hexagonal boron nitride and the melamine foam skeleton treated with silane coupling agent are laminated, a continuous, uniform and dense heat conduction path is formed on the foam surface, which is beneficial to the heat transfer.
[0121] from Figure 3 It can be seen that after the boron nitride foam skeleton is treated with polydopamine, it can form a good connection with the magnetic ferroferric oxide / porous graphene, and the synergistic effect between the two is conducive to the improvement of the material's wave absorption and thermal conductivity.
[0122] from Figure 4 It can be seen that the silicone rubber prepared in Example 1 has a minimum reflection loss of -54.30 dB at 14.32 GHz at a thickness of 2.5 mm, and an effective absorption bandwidth of 6.76 GHz. The silicone rubber has excellent wave absorption and thermal conductivity.
[0123] from Figure 5 It can be seen that compared with the comparative sample melamine foam, the thermal conductivity of the silicone rubber prepared in Example 1 is significantly improved.
[0124] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a boron nitride / polydopamine / porous graphene modified foam, characterized in that: The following steps are involved: (1) immersing the polymer foam in a modified boron nitride solution and freeze-drying the solution to obtain a boron nitride modified foam; (2) immersing the boron nitride modified foam in a dopamine solution and vacuum drying to obtain a boron nitride / polydopamine modified foam; (3) irradiating the carbon-containing film with a laser and scraping off the formed three-dimensional porous graphene to obtain porous graphene; (4) Immersing the boron nitride / polydopamine modified foam in a porous graphene solution and vacuum drying to obtain a boron nitride / polydopamine / porous graphene modified foam.
2. The preparation method according to claim 1, characterized in that: In step (1), the polymer foam is selected from at least one of melamine foam and polyurethane foam; Preferably, the polymer foam is treated with a silane coupling agent; Preferably, the silane coupling agent is selected from at least one of KH-550, KH-551, and KH-560; Preferably, the silane coupling agent is an aqueous solution of silane coupling agent with a concentration of 0.02 to 0.1 g / mL.
3. The preparation method according to claim 1, characterized in that: In step (1), the modified boron nitride is hydroxy boron nitride, which is obtained by treating hexagonal boron nitride with a strong base; Preferably, the strong base is selected from at least one of sodium hydroxide, potassium hydroxide, calcium hydroxide and barium hydroxide; Preferably, the particle size of the hexagonal boron nitride is 1 to 2 μm; Preferably, the concentration of the strong base is 5 to 10 mol / L, the treatment temperature is 80 to 120°C, and the treatment time is 8 to 16 hours; Preferably, the modified boron nitride solution is an aqueous solution of hydroxyboron nitride with a concentration of 2 to 10 mg / mL.
4. The preparation method according to claim 1, characterized in that: In step (2), the dopamine solution comprises dopamine hydrochloride and Tris buffer; Preferably, the dosage ratio of dopamine hydrochloride to Tris buffer is (0.05-0.15) g:25 mL; Preferably, the pH value of the Tris buffer is 7.5-8.
5.
5. The preparation method according to claim 1, characterized in that: In step (3), the carbon-containing film is a film made of at least one of a synthetic polymer and a natural polymer; Preferably, the carbon-containing film is a film made of synthetic high molecular polymer, natural high molecular polymer and metal salt; Preferably, the synthetic high molecular polymer is selected from at least one of polyethersulfone, polyimide, polyethylene terephthalate, polystyrene, and phenolic resin; Preferably, the natural high molecular polymer is selected from at least one of lignin, cellulose, starch, polysaccharide, chitosan, chitin and derivatives thereof; Preferably, the metal salt is selected from at least one of iron salts, nickel salts, copper salts and molybdenum salts.
6. The preparation method according to claim 1, characterized in that: In step (3), the laser is at least one of a fiber laser, a solid laser, a gas laser, a semiconductor laser, and a liquid laser; Preferably, the laser irradiation power is 16-25W, the scanning speed is 180-450mm / s, the jump speed is 100-1000mm / s, the Q frequency is 1-10KHz, the scanning line spacing is 0.06-0.12mm, the spot size is 60-100μm, and the focal length is set to 0.5-3mm above the film surface.
7. Boron nitride / polydopamine / porous graphene modified foam prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the boron nitride / polydopamine / porous graphene modified foam according to claim 7 as a wave absorbing and heat conducting material.
9. A wave-absorbing and heat-conducting silicone rubber, characterized in that: The wave-absorbing and heat-conducting silicone rubber comprises silicone rubber and the boron nitride / polydopamine / porous graphene modified foam described in claim 7.
10. A method for preparing a wave-absorbing and heat-conducting silicone rubber, characterized in that: Firstly, liquid silicone rubber is cast on the boron nitride / polydopamine / porous graphene modified foam, and then heated and vulcanized to obtain the wave absorbing and heat conducting silicone rubber; Preferably, the liquid silicone rubber is a mixture of vinyl silicone oil, hydrogen-containing silicone oil, MQ silicone resin, an inhibitor and a catalyst; Preferably, the inhibitor is selected from at least one of vinyl ring bodies and alkynols; the catalyst is selected from at least one of platinum catalysts and organotin catalysts; Preferably, the mass ratio of the vinyl silicone oil, hydrogenated silicone oil, MQ silicone resin, inhibitor and catalyst is 100:(14.67-17.34):(10.88-12.68):(0.05-0.08):(0.05-0.15); Preferably, the heating vulcanization is carried out in a vacuum drying oven, firstly evacuating the oven at room temperature for 1 to 3 hours and then heating the oven to 100 to 120° C. and evacuating the oven for 1 to 3 hours.